2015
DOI: 10.1007/s10526-015-9691-2
|View full text |Cite
|
Sign up to set email alerts
|

Spider foraging strategies dominate pest suppression in organic tea plantations

Abstract: Organic management of crops generally leads to greater predator richness. However conservation of natural enemy species richness does not consistently strengthen herbivore suppression. Here we explored relationships between abundance and diversity of predatory spiders with two distinct foraging strategies and their prey, leafhopper pests. In three organic tea plantations, we investigated abundance of these spiders, and population dynamics of an important tea green leafhopper pest, Empoasca vitis (Homoptera: Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Hoffman et al [12] suggested that factual concernment and perceived concern are the two important factors that determine consumers' intention to purchase organic foods. Several other studies also investigated factors regarding to health and environmental protection as main antecedents of organic food consumption [13,14,[16][17][18]20,21]. In sum, these studies have provided rich evidence on the factors that influence consumers' purchase behavior toward organic foods.…”
Section: Prior Studies On Organic Tea and Organic Foodsmentioning
confidence: 99%
“…Hoffman et al [12] suggested that factual concernment and perceived concern are the two important factors that determine consumers' intention to purchase organic foods. Several other studies also investigated factors regarding to health and environmental protection as main antecedents of organic food consumption [13,14,[16][17][18]20,21]. In sum, these studies have provided rich evidence on the factors that influence consumers' purchase behavior toward organic foods.…”
Section: Prior Studies On Organic Tea and Organic Foodsmentioning
confidence: 99%
“…In recent years, several integrated pest management (IPM) approaches have been tested to control E. vitis population density, such as the use of nonsusceptible cultivars, and techniques of landscape management to favor the occurrence of predators and parasitoids (Decante & van Helden, 2006;Pavan & Picotti, 2009;Fornasiero et al, 2015;Liu et al, 2015). However, none of them have been applied extensively to the field and population control of E. vitis is still achieved mainly with pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…In tea fields, Kosugi (2003) has reported the predatory quality of Trachelas japonicus Bösenberg & Strand (Araneae: Corinnidae) and Philodromus subaureolus Bösenberg & Strand (Araneae: Philodromidae) on Empoasca onukii Matsuda (Hemiptera: Cicadellidae), keeping their populations under control. Spiders can control the density of leafhoppers in tea fields ( Liu et al 2015 ), with larger spider populations effectively reducing populations of E. onukii and Scritothrips dorsalis Hood (Thysanoptera: Thripidae) ( Goto et al 1995 ). Shiraki and Ohashi (1992) have shown that the population density of spiders and other natural enemies are higher in pesticide-free tea fields than in those sprayed with pesticides.…”
mentioning
confidence: 99%